A model for dispute resolution in Europe - Hodges, C (2011)
This policy brief addresses alternative dispute resolution mechanisms in Europe to propose an integrated, holistic approach to encompass the range of mechanisms for resolving disputes, including ombudsmen, compensation schemes, business codes of conduct, complaint boards, and other pathways. In response to the increase in collective redress, a European alternative to US-style class actions is presented by way of a model for the alignment of the various existing systems to promote good practice. The best ADR mechanisms do not just lead to resolution of disputes but also deliver information, incentives, and pressure to maintain and improve performance standards. Hence, dispute resolution systems should be designed to play their part within wider regulatory structures, providing lessons that can be used to influence future behaviour.